The lithium stellarator experiment. TJ-II as a benchmark - Tabarés, F.L.; Tafalla, D.; Ferreira, J.A.; Ochando, M.A.; Medina, M.; Ascasibar, E.; Estrada, T.; Fuentes, C.; García-Cortés, I.; Guasp, J.; Linier, M.; Pastor, I.; et al. (Вопросы атомной науки и техники, 2008)
In the last years, lithium wall conditioning has been carried out in several fusion devices (Tokamaks, Compact Toruses) by different techniques, providing in many instances record values of plasma parameters and enhanced plasma reproducibility. Behind these findings are the low recycling, low contamination and non-coronal enhanced radiative power dissipation properties of Li. Stellarators are best suited for reactor concepts as far as they basically free from extreme thermal load events. However, the potential problem of impurity accumulation must be taken into account. Therefore, the use of low Z elements as PFC would be highly desirable. In the present work, the plasma performance of the TJ-II Heliac under Li-coated wall conditions with lithium is described. Compared to previous coatings, lithium has produced the best plasma performance to date, leading to the achievement of record values in plasma density and energy confinement. In the present work, the impact of the Li coating operation on reactor relevant issues, such as particle exhaust and retention, high-density operation, confinement characteristics and plasma wall interaction issues is stressed.